Rehabilitación urbana sostenible, el Sembrador 1 rehabilitación sostenible de las áreas de cesión para espacio público y equipamiento: (2024)
The present research work is located in the municipality of Palmira, in the sower stage 2 sector. Having as its general objective a sustainable urban design proposal for the rehabilitation of the transfer areas intended for green areas and equipment in the object place study.